2006
DOI: 10.1063/1.2337103
|View full text |Cite
|
Sign up to set email alerts
|

High temperature dc field poling effects on the structural phase transformations of (1−x)Pb(Mg1∕3Nb2∕3)O3–xPbTiO3 single crystal with morphotropic phase boundary composition

Abstract: The complex dielectric permittivity of the morphotropic phase boundary ͓001͔-oriented PMNx % PT single crystal with x = 33%, grown by the modified Bridgman technique, has been investigated as a function of both temperature and dc poling field. Structural phase transformation sequence is discussed in the light of polarization rotation process. A remarkable shift in the rhombohedral-tetragonal phase transition temperature is observed with changing of the poling field. It is found that high temperature poled stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The other factor that may influence CP dynamics in the present case is realignment/movement of domain walls in the FE matrix resulting from the reorientation of polarization direction from ͓001͔ to ͓111͔. 18 This explanation is supported by similar remarks about PZN-8%PT ͑Ref. 19͒ and PMN-60%PT ͑Ref.…”
Section: ͑Pmn-xpt͒supporting
confidence: 73%
“…The other factor that may influence CP dynamics in the present case is realignment/movement of domain walls in the FE matrix resulting from the reorientation of polarization direction from ͓001͔ to ͓111͔. 18 This explanation is supported by similar remarks about PZN-8%PT ͑Ref. 19͒ and PMN-60%PT ͑Ref.…”
Section: ͑Pmn-xpt͒supporting
confidence: 73%
“…The crystalline symmetry group of M phase is the subgroup of both T phase and R phase. Therefore, the phase transition between R phase and T phase becomes acceptable from the viewpoint of crystalline symmetry [6][7][8][9]. Furthermore, the M phase has been considered to be the origin of the giant piezoelectric properties of PZT ceramics with the composition in the vicinity of MPB owing to the symmetry-allowed rotation of the polarization direction of M phase [1,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Before the phase transition, the ACP samples poled with 20 AC cycles has a maximum dielectric constant value (ε 33,max ∼ 40,000), which is much higher than the DCP sample (ε 33,max ∼ 20,000) at the same temperature. It has been reported that the poled rhombohedral PMN-x%PT has a phase transition sequence of R → T → C during the zero field heating [36]. In this work, the similar dielectric constant curve in Figure 4(a) shows the phase transition temperatures of DCP PMN-30%PT single crystal are 90°C (363 K) for R → T and 130°C (403 K) for T → C. Comparingly, ACP samples have the same phase transition temperature near 90°C and 130°C, while extra anomalies of dielectric constant drops at 92°C ∼ 96°C (365 K ∼ 369 K) are shown in dielectric constant curves of ACP samples, as shown in Figure 4(b).…”
Section: Introductionmentioning
confidence: 99%